Parameters affecting 5-hydroxymethylfurfural exposure from beer - Viegas, Olga (2018)
5-Hydroxymethylfurfural (HMF) is generated during food and beverage heating processes and/or storage. Its daily intake, estimated as 4-10mgday(-1), is several orders of magnitude higher than other process contaminants. Beer can be of relevance to the evaluation of HMF exposure; however, the information concerning its occurrence in different types of beer and during product storage is scarce. Therefore, the major goal of this work was to assess the amounts of HMF in different commercial beers, as well as the impact of storage, to deepen knowledge about the contribution of beer to HMF exposure. Blonde beers presented a mean content of 4.29 +/- 1.05mgL(-1), which was significantly lower (P0.05) than those obtained for amber (6.84 +/- 0.75mgL(-1)) and dark beers (6.99 +/- 0.52mgL(-1)). Additionally, to study kinetic of HMF formation, fresh pilsner beers were stored at 30, 40 and 50 degrees C during 40days; a zero-order reaction was observed. The dependence of the rate constant on temperature was described by the Arrhenius equation and calculated activation energy was 101.85kJmol(-1). Storage can increase drastically HMF content, which means higher exposure for consumers. Thus, beer contribution to HMF exposure should not be neglected, since the intake of 1L of beer entails a consumption of 4-7mg of HMF or even more, depending on storage time and temperature.